Efficacy of a Therapeutic Diet on Dogs With Signs of Cognitive Dysfunction Syndrome (CDS): A Prospective Double Blinded Placebo Controlled Clinical Study - Pan, Yuanlong; Landsberg, Gary; Mougeot, Isabelle; Kelly, Stephanie; Xu, Hui; Bhatnagar, Sandeep; Gardner, Cari L.; Milgram, Norton W. (Frontiers in Nutrition, 2018)
Cognitive dysfunction syndrome (CDS) is a common condition in senior dogs, which may be analogous to dementia such as Alzheimer’s disease (AD) in people. In humans, AD has been associated with many risk factors such as reduced cerebral glucose metabolism, docosahexaenoic acid (DHA) deficiency, chronic oxidative stress, and chronic inflammation. By targeting some of these risk factors, we have developed two nutritional solutions (medium chain triglyceride, MCT and Brain Protection Blend, BPB) to enhance cognitive function and slow aging-induced cognitive decline. These have been positively evaluated in colony housed senior dogs and cats. The objective of this clinical study was to evaluate the effects of diets with MCTs and the BPB on client-owned dogs with CDS. Participating veterinary clinics screened senior dogs for signs of CDS as determined by a Senior Canine Behavior Questionnaire and a Canine Medical Health Questionnaire. Eighty-seven dogs were randomly enrolled into one of three diet groups with 29 dogs per group: Control, 6.5% MCT oil + BPB (6.5% MCT diet), 9% MCT oil + BPB (9% MCT diet). Diets were fed for a period of 90 days, and each dog’s CDS signs were re-evaluated at day 30 and day 90. All 6 categories of the CDS signs were significantly improved (p <0.05) in the dogs given the 6.5% MCT diet at the end of the 90-day study. Control only improved in 4 out 6 categories. The 9% MCT diet only improved in dogs that accepted the diet. The results from this dog study confirm the benefits of MCT and BPB in managing clinical signs of CDS in dogs. The results support our hypothesis that targeting known risk factors associated with brain aging and AD is able to improve symptoms of CDS in dogs. These data may facilitate the development of similar nutrient blend to manage MCI and AD.